EFEKTIVITAS MEDIA PEMBELAJARAN INTERAKTIF BERBASIS CANVA PADA MATERI PECAHAN DI SD N 327 SINUNUKAN - Torang Siregar; Amir, Almira; Adinda, Anita (Dedikasi: Jurnal Pengabdian kepada Masyarakat, 2023)
Abstract : This study aims to produce interactive media assisted by the Canva application for valid, practical and effective grade V elementary school fractional material. This research uses the Research and Development (R&D) method with the ADDIE model which consists of 5 stages, namely analysis, design, development, implementation, and evaluation. Data is obtained in 3 ways, namely: observation, interview, and questionnaire. This media was validated by material experts, media experts and conducted feasibility tests on grade V elementary school students totaling 30 students. The results of material expert validation obtained a presentation score of 93% with a very decent category and the results of media expert validation obtained a presentation score of 93% with a very decent category. Based on the results of student responses, a percentage score of 89% can be obtained with a very decent category. So it can be concluded that in this study Canva-based interactive learning media is very feasible to be used as a learning resource by grade V elementary school students.